1996
DOI: 10.1017/s1041610296002657
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Temporal Course of Probable Alzheimer's Disease: A 5-Year Prospective Study

Abstract: Alzheimer's disease (AD) is asociated with an increased mortality in comparison with aged control populations. The relationship between the clinical and the temporal course of AD has not been well studied over significant intervals. Community residing patients with probable AD (N = 103, 42 men, mean age = 70.2 ± 8.0 years) were studied at baseline on demographic and clinical variables, including measures of global deterioration (Global Deterioration Scale; GDS), mental status and cognition (e.g., Mini-Mental S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 29 publications
3
94
0
4
Order By: Relevance
“…25,26,[36][37][38][39][40][41][42][43][44] Many studies have reported shorter survival for men with dementia as compared with women. 42, 45-48 Regarding ethnic differences, the literature is mixed, with some studies finding higher mortality for Caucasians with AD 26,49 and some others reporting no race differences.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,[36][37][38][39][40][41][42][43][44] Many studies have reported shorter survival for men with dementia as compared with women. 42, 45-48 Regarding ethnic differences, the literature is mixed, with some studies finding higher mortality for Caucasians with AD 26,49 and some others reporting no race differences.…”
Section: Discussionmentioning
confidence: 99%
“…[190][191][192] Secondo uno studio effettuato in comunità, su 100 persone ultra65enni con demenza definita allo stadio FAST > 7a la sopravvivenza media è di 1,85 anni (95%CI 1,64-2,06), a 6 mesi del 86,6%; a 12 mesi del 77,6%; a 18 mesi del 70,1% e a 24 mesi del 64,2%. …”
Section: Functional Assessment Staging (Fast)unclassified
“…[6][7][8] AD disease progression is not a uniform process; rates of decline vary widely, and there is an enormous range of disability that is largely dependent on the stage of severity.…”
Section: Disease Progression: Moderate To Severe Alzheimer's Diseasementioning
confidence: 99%
“…8,14 Staging tools delineate the course of AD and provide a means whereby an individual with AD may be placed along a continuum of decline. Because multiple domains are affected by AD, a variety of staging tools have been developed; some evaluate cognition, others assess global severity, and others focus on functional status.…”
Section: Staging Tools For Determining Alzheimer's Disease Severitymentioning
confidence: 99%